Comparison of four different lasers for acne scars: Resurfacing and fractional lasers. Issue 4 (April 2016) - You, Hi-Jin; Kim, Deok-Woo; Yoon, Eul-Sik; Park, Seung-Ha
Summary: Background: Acne scars are common and cause cosmetic problems. There is a multitude of treatment options for acne scars, including dermabrasion, chemical peeling, and fillers, but the advent of laser technology has greatly improved the treatment of acne scars. Although several laser systems are available, studies comparing their efficacy are limited. This study compares the results of treatments using resurfacing (carbon dioxide, CO2 ; erbium-doped yttrium aluminum garnet, Er:YAG) versus fractional (nonablative fractional laser, NAFL; ablative fractional laser, AFL) lasers. Methods: A retrospective photographic analysis of 58 patients who underwent laser treatment for facial atrophic acne scars was performed. Clinical improvement was assessed by six blinded investigators with a scale graded from 0 to 10. Adverse events were also noted. Results: Mean improvement scores of the CO2, Er:YAG, NAFL, and AFL groups were 6.0, 5.8, 2.2, and 5.2, respectively. The NAFL group showed a significantly lower score than the other groups. The mean number of treatments was significantly greater in the fractional laser groups than in the resurfacing laser groups. The resurfacing laser groups had a prolonged recovery period and high risk of complications. The Er:YAG laser caused less erythema or pigmentation compared to the CO2 laser. Conclusions: Although the CO2 laser, Er:YAG laser, and AFL improved the acne scars, the CO2 laser had a greater downtime. Three consecutive AFL treatments are as effective as a single treatment with resurfacing lasers, with shorter social downtime periods and less adverse effects.